Developing Performance Tests to Measure Digital Skills: Lessons Learned From a Cross-National Perspective - Ester van Laar; Alexander J. A. M. van Deursen; Ellen J. Helsper; Luc S. Schneider (Media and Communication)
This article discusses the development of task-based performance tests designed to measure digital skills among children aged between 12 and 17 years old. The tasks reflect authentic everyday situations to evaluate skill levels. The primary objective is to design performance tests that provide a comprehensive understanding of children’s digital skills. The tests cover three distinct skill dimensions: (a) information navigation and processing; (b) communication and interaction; and (c) content creation and production. These include several subdimensions, offering a detailed perspective on children’s digital skills. The development process itself revealed several methodological challenges that needed to be addressed, yielding valuable lessons for future applications. Key lessons from our cross-national experiences include the importance of involving children early in the design process, using a combination of open-ended and closed tasks, and allocating ample time to walk through the coding scheme.